Islamic Intellectual Tradition in Indonesia - Muhammaddar; Muhaini (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
The Islamic intellectual tradition in Indonesia results from interactions between traders from the Arabian peninsula and indigenous Indonesian communities. This interaction brings the need for intellectual development that considers the social, cultural, and economic differences between the two. Ijtihad is an important point in forming and developing the Islamic intellectual tradition in Indonesia, which integrates local wisdom with Islamic teachings. The flow of Islamic intellectualism in Indonesia began and developed in Aceh, reflected in the influence of Islam on Acehnese customs. Malacca also played an important role as a center for trade and the spread of Islam in the archipelago. The Islamic education system in Indonesia developed from basic to in-depth levels, with the influence of teaching methods introduced during the Abasyiah dynasty. Although the process of mass Islamization only accelerated in the 12th to 16th centuries AD, the Islamic intellectual tradition continued to develop through intellectual centers such as Samudera Pasai, Malacca, and Aceh Darussalam, as well as in Java with the presence of the Wali Songo.